(untitled) (Experimental biology, 2023)
The article presents the results of the research conducted by the authors on the territory of the Ile-Alatau GNPP in 2020-2021. Research works are devoted to the fauna, biology and ecology of hemiptera in the park. Hemiptera, or bedbugs, are the most numerous group of insects of great practical importance. Hemiptera are widespread in the Ile-Alatau SNNP. When collecting the material, standard entomological methods were used - collecting with an entomological net, catching small insects with an exhauster, at night on an artificial light source, manual collection, etc. As a result of field scientific research on the territory of the Ile-Alatau State National Natural Park, 26 species belonging to 6 families of hemiptera of the Pentatomomorpha II infra-order have been identified. Among them, the Rhopalidae family predominates in species composition - 9 species, Coreidae - 6 species, Acanthosomatidae - 4 species, Alydidae and Cydnidae – 3 species each, and only 1 species is known from the Plataspidae family. According to life forms, the bugs of the Ile-Alatau GNPP are distributed into 7 groups: hortobionts (15 species), eurychortobionts (1 species), dendrobionts (4 species), dendrobionts (2 species), herpetobionts (2 species), herpetobionts (1), geo-herpetobionts (1 species). According to trophic specialization, they are divided into phytophages (29 species, of which polyphytophages – 13 species, wide oligophytophages - 10 species, narrow oligophytophages - 3 species). The hemiptera of the Ile-Alatau GNPP are divided into 3 groups according to the number of generations per year: monovoltine - 16 species, bivoltine - 7 species, 2-3 generations per year - 3 species. There are 23 species with mesophilic ecology in the research area, 3 species – meso-xerophile. Among the hemiptera of the Ile-Alatau GNPP, 23 species overwinter in the imago stage, 1 species in the larval stage, and 1 species in the egg stage, eggs and larvae overwinter - 1 species.